Kearifan lokal dalam tradisi sedekah bumi sebagai cerminan harmoni manusia dan alam - yanah, muda (Maliki Interdisciplinary Journal, 2026)
The Sedekah Bumi tradition is a form of local wisdom that thrives and develops within Indonesian agrarian society. This tradition is not merely interpreted as an annual cultural ritual, but also as a representation of the harmonious relationship between humans, nature, and God. The values of local wisdom contained in the Sedekah Bumi tradition serve as a mechanism for maintaining harmony between humans and nature. This study employs the literature review method, examining journal articles, academic books, and research reports. The results of the review indicate that the Sedekah Bumi tradition encompasses religious, ecological, social, and cultural values that function as a mechanism for moral control over society’s behavior toward the environment. Furthermore, this tradition holds strategic potential as a basis for environmental education and for strengthening sustainable development rooted in local culture. This article is expected to provide both theoretical and practical contributions to the development of studies on local wisdom in the context of the global environmental crisis.